Risk Management and Performance of Health Supply Chain Projects in Uganda. The Case of Uganda Health Supply Chain Project - Wasswa, John Hans; Kwatampora, Rose; Bwanika, Godfrey; Namulindwa, Angella (International Journal of Science and Research (IJSR), 2018)
This study aimed at assessing the effect of risk management on performance of Health supply chain projects in Uganda using a case of Uganda Health Supply Chain project. The specific objectives were; to determine the effect of risk identification on the performance of health supply chain projects in Uganda; assess the effect of risk analysis on the performance of health supply chain projects in Uganda; investigate the extent to which planning for risk management affects the performance of health supply chain projects in Uganda and lastly determine the extent to which risk response and control affect performance of health supply chain projects in Uganda. The study was based on the normative decision theory of risk management and the positivism research philosophy. It employed a cross-sectional study design and adopted both quantitative and qualitative approaches. A total sample population of 196 was used. Primary data was collected using self-administered questionnaires for quantitative data and analyzed using STATA while qualitative data was collected using an interview guide and analyzed using the content analysis method. In this study, four hypotheses were tested using the logistic regression technique employing the p-value and odds ratio approach. Findings revealed a good understanding of the risk management concept among a majority of the respondents, but however, there was a low adoption of standard risk management practices. The study further revealed that a majority of the investigated practices had a significant effect on the level of time, cost and quality performance of health supply chain projects in Uganda. The study concluded that performance of health supply chain projects in Uganda has been below average due to low adoption of standard risk management practices. The study recommended prioritizing risk management high on the project’s management agenda by all supply chain projects in Uganda
Keywords: Risk management; Performance; Health supply chain projects; Risk identification